Voice of freedom : Fannie Lou Hamer, spirit of the civil rights movement - Weatherford, Carole Boston, 1956- (Candlewick Press, 2015)
Presents a collage-illustrated treasury of poems and spirituals inspired by the life and work of civil rights advocate Fannie Lou Hamer.